Senior High School Students’ Anxiety and Performance in Learning English - Sansaluna, Saima; Bawa, Lydia; Camua, Amour; Untong, Leonel (Advances in Social Sciences Research Journal, 2021)
This study focused on the anxiety and performance of the students in learning English specifically in speaking. It sought to find out anxieties and its causes that affect their English performance in terms of inter-language phonology, grammar and meaning system. The study covered the use of Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz et al. (1986) that measure the English learners’ anxiety levels while learning English in the classroom. The respondents of the study were the selected Grade 12 senior high school students from the selected public schools in Maguindanao Division, Philippines. Descriptive-correlational survey method was used in the study. The findings show that English language speaking anxiety does exist among Senior High School students in Maguindanao Division and their level of anxiety in learning English is high. It is further concluded that students’ anxiety levels in speaking English in terms of inter-language phonology, inter-language grammar and inter-language meaning system contributed to students’ performance in learning in English.